2016
DOI: 10.1111/imj.13139
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban versus enoxaparin in the prevention of venous thromboembolism following total knee arthroplasty: a single‐centre, single‐surgeon, retrospective analysis

Abstract: Compared with enoxaparin, thromboprophylaxis with apixaban resulted in a lower VTE incidence and fewer haemorrhagic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Given reports of high VTE rates in Australia [3], VTE pharmacoprophylaxis has remained as the main focus of clinical interest. Recent studies have indicated VTE rates in Australia range from 0.7% (in-hospital) to 4.7%, [26, 27] almost comparable to the rates of bleeding (1.5–6.7%) [27, 28]. Although the generalisability of these figures remains uncertain, it does speak to the issue raised by Campbell et al that bleeding and adverse events were seemingly under-emphasised in pharmacoprophylaxis studies [29].…”
Section: Discussionmentioning
confidence: 99%
“…Given reports of high VTE rates in Australia [3], VTE pharmacoprophylaxis has remained as the main focus of clinical interest. Recent studies have indicated VTE rates in Australia range from 0.7% (in-hospital) to 4.7%, [26, 27] almost comparable to the rates of bleeding (1.5–6.7%) [27, 28]. Although the generalisability of these figures remains uncertain, it does speak to the issue raised by Campbell et al that bleeding and adverse events were seemingly under-emphasised in pharmacoprophylaxis studies [29].…”
Section: Discussionmentioning
confidence: 99%
“…In three of the included studies, direct thrombin-and factor Xa inhibitors were used as thromboprophylaxis, including dabigatran, 17 rivaroxaban, 18 and apixaban. 19 In patients receiving dabigatran, the risk within 90 days of hospital admission was 0.2% (THA) to 1.1% (TKA) for DVT, 0.4% (TKA) to 0.5% (THA) for PE, and 0% for death. 17 The dabigatran dose was 110 mg four hours following surgery, and then 220 mg daily for 28 days (THA) or 14 days (TKA).…”
Section: Direct Thrombin-and Factor Xa Inhibitorsmentioning
confidence: 92%
“…The main variables for each study are shown in Table 1, and include the following specific prophylactic agents: 1) warfarin [10][11][12] ; 2) low molecular weight heparins (LMWHs) (enoxaparin, dalteparin, and nadroparin) [13][14][15][16][17] ; 3) unfractionated heparin 13 ; 4) direct thrombin-and factor Xa inhibitors (dabigatran, rivaroxaban, and apixaban) [17][18][19] ; 5) acetylsalicylic acid 11,12,14,20,21 ; and 6) fondaparinux. 13 Below, we summarize the findings presented in Table 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…In recent years, new anticoagulant oral preparations have been developed. Apixaban is a new potent oral FXa inhibitor that can rapidly combine with FXa and transform prothrombin into thrombin 89. One study has shown that apixaban can significantly reduce the incidence of DVT and the associated mortality after orthopedic surgery 10.…”
Section: Introductionmentioning
confidence: 99%